2015
DOI: 10.1089/ten.tea.2014.0408
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of rAAV-hTERT-Transducted Nucleus Pulposus Cells in Early Stage of Intervertebral Disc Degeneration: A Study in Canine Model

Abstract: In 12 weeks of observation, rAAV-hTERT-transducted NPCs could delay the degeneration process in the canine model which was superior than the capacity of NPCs in preserving structure integrity, content of extracellular matrix, and mechanical stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…NP is predominantly composed of collagen-II and aggrecan, and the decrease of collagen-II is associated with disc degeneration (23,24). The present study demonstrated that GDF-5 prevented the loss of collagen-II and aggrecan that was induced by LPS.…”
Section: Discussionsupporting
confidence: 60%
“…NP is predominantly composed of collagen-II and aggrecan, and the decrease of collagen-II is associated with disc degeneration (23,24). The present study demonstrated that GDF-5 prevented the loss of collagen-II and aggrecan that was induced by LPS.…”
Section: Discussionsupporting
confidence: 60%
“…Inhibitors of MMPs and ADAMTSs have a therapeutic effect on OA ( Gilbert et al, 2007 ) and IDD ( Leckie et al, 2012 ) in vitro and in vivo . Collagen-II and aggrecan are the main components of nucleus pulposus, and the reduction of collagen-II content is highly correlated with disc degeneration ( Shi et al, 2015 ; Kozaci et al, 2006 ). Our study shows that cordycepin can both prevent LPS-induced collagen-II and aggrecan loss and promote their synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It showed an increase in Col II (73 pg/mg) than Col I (61 pg/mg) in different lumbar segments of group A (L1, L2) and much higher Col I content (266 pg/mg) in group B (L3, L4) than other groups compared with group C (L5, L6) and A (L1, L2). Therefore, (RAAV)-(hTERT)-(NPCs) increased the ECM content and helped in delaying the degeneration process in the canine model . It has also been shown to restore basic IVD function to evade difficulties generated by decompressive procedures and stabilization.…”
Section: Methods Of Developing In Vivo Ivd Injury Modelmentioning
confidence: 99%
“…Therefore, (RAAV)-(hTERT)-(NPCs) increased the ECM content and helped in delaying the degeneration process in the canine model. 85 It has also been shown to restore basic IVD function to evade difficulties generated by decompressive procedures and stabilization. A novel nucleus pulposus prosthesis (NPP) exhibits a range of motion (ROM), neutral zone (NZ), and neutral zone stiffness (NZS) when subjected to cycling loading, NZS restored the functionality, and could enhance the functionality of IVDD.…”
Section: Modelmentioning
confidence: 99%